Se former aux humanités numériques par les données ouvertes : les chaînes infométriques de Patent2Net (P2N) - David Reymond; Jean-Max Noyer (Humanités Numériques)
The digital humanities express a double transformation: an anthropotechnical metamorphosis of the world and a changeover in intellectual practices in all their dimensions. New memories, new types of writing, the growing importance of algorithms: these evolutions constantly modify how we design editorial modes, process corpora, make maps, or access conceptual and semantic networks, as well as reading and writing practices, and hermeneutic capabilities. These skills are relatively new, and they are often difficult to apply in front of an audience with varying levels of interest and technical knowledge. In this context, we have developed and tested a set of tools that allow us to develop many of these skills in the treatment of economic, technological, historical or organisational data, and, moreover, multimodal data (text, images, graphs). Through the analysis of a corpus of patents, which we place in the field of humanities, we discuss the operational and conceptual pedagogical contributions of this approach based on real data.